Numerical Simulations of the Effect of Cold Fuel Temperature on In-Nozzle Flow and Cavitation Using a Model Injector Geometry - Bontitsopoulos,S; Hamzehloo,A; Aleiferis,P; Cracknell,R (SAE Technical Papers, 2020)
Large Eddy Simulations (LES) were performed using a 3D model of a step nozzle injector. The focus has been on modelling injections with pentane, chosen as a representative single component of the high-volatility components in gasoline. The influence of fuel temperature was investigated with comparisons primarily made between 20 deg C and -10 deg C. The test cases provided a description of the in-nozzle cavitating flow and the macroscopic near-nozzle spray jet structure across different cavitation regimes in order to shed light on engine cold-start effects, a phenomenon prevalent in a number of combustion applications, albeit not extensively studied. The results showed that the size and intensity of the cavitation features tend to become suppressed as the temperature of the fuel decreases. The 20 deg C cases (supercavitating regime) depicted a sporadic shedding of vapour nuclei from a continuous cavitation region that extended to the nozzle outlet surface. Collapse-induced wave dynamics in that region caused a transient entrainment of air from the discharge chamber towards the nozzle inlet. The extent of air entrainment appeared noticeably reduced at the coldest temperature of -10 deg C (incipient cavitation regime) due to the shorter length of the cavitation region, which impeded the backflow of air. Temporally averaged data showed that the near-nozzle jet appearance was also affected by the fuel temperature. The -10 deg C case produced a relatively symmetric jet, in contrast to the supercavitating cases that demonstrated an increased opening angle and a concave surface on the side of the step nozzle edge due to the intense cavitation and parallel air entrainment.